Selected proteolytic aspects as targets to combat ticks and tick borne pathogens - Hartmann, David (Jihočeská univerzita, 2021)
Ticks and tick-borne diseases (TBD) represent a growing global burden for both human and animal health. Tick-host-pathogen interactions have evolved through dynamic processes that accommodated the genetic traits of the hosts, pathogens transmitted, and the vector tick species that mediate their development and survival. As in other parasites, proteases and proteolysis have been found as one of the key factors in this interaction triangle. This thesis is focused on selected proteolytic aspects of tick and tick-borne diseases: (i) processing of host blood as a source of nutrients and energy (hematophagy) as a continuum of the long-term goal of the Laboratory of Vector Immunology, that established the currently accepted model of multienzyme degradation of host blood proteins by ticks (ii) proteases in innate immunity (iii) validation of Babesia proteasome as a potential therapeutic target against the tick transmitted apicomplexan parasites.
Selected proteolytic aspects as targets to combat ticks and tick borne pathogens
Keywords: klíště; proteázy; trávení krve; parazit; babesia; ixodes ricinus; ixodes scapularis; proteázom; tick; protease; peptidase; blood-digestion; blood digestion; blood-feeding; blood feeding; ixodes ricinus; ixodes scapularis; babesia; proteasome; parasite; blood